An Allosteric Inhibitory Site Conserved in the Ectodomain of P2X Receptor Channels - Ase, Ariel R.; Therrien, Éric; Séguéla, Philippe (Frontiers in Cellular Neuroscience, 2019)
P2X receptors constitute a gene family of cation channels gated by extracellular ATP. They mediate fast ionotropic purinergic signaling in neurons and non-excitable cell types in vertebrates. The highly calcium-permeable P2X4 subtype has been shown to play a significant role in cardiovascular physiology, inflammatory responses and neuro-immune communication. We previously reported the discovery of a P2X4-selective antagonist, the small organic compound BX430, with submicromolar potency for human P2X4 receptors and marked species-dependence (Ase et al., 2015). The present study investigates the molecular basis of P2X4 inhibition by the non-competitive blocker BX430 using a structural and functional approach relying on mutagenesis and electrophysiology. We provide evidence for the critical contribution of a single hydrophobic residue located in the ectodomain of P2X4 channel subunits, Ile312 in human P2X4, which determines blockade by BX430. We also show that the nature of this extracellular residue in various vertebrate P2X4 orthologs underlies their specific sensitivity or resistance to the inhibitory effects of BX430. Taking advantage of high-resolution crystallographic data available on zebrafish P2X4, we used molecular dynamics simulation to model the docking of BX430 on an allosteric binding site around Ile315 (zebrafish numbering) in the ectodomain of P2X4. We also observed that the only substitution I312D (human numbering) that renders P2X4 silent by itself has also a profound silencing effect on all other P2X subtypes tested when introduced at homologous positions. The generic impact of this aspartate mutation on P2X function indicates that the pre-TM2 subregion involved is conserved functionally and defines a novel allosteric inhibitory site present in all P2X receptor channels. This conserved structure-channel activity relationship might be exploited for the rational design of potent P2X subtype-selective antagonists of therapeutic value.